Section 2: Patient Records: Integrating Bioinformatics into Clinical Practice: Progress and Evaluation - Lang, E.; Managing Editor for the IMIA Yearbook Section on Bioinformatics (Yearbook of Medical Informatics, 2007)
To summarize current excellent research in the field of bioinformatics.Synopsis of the articles selected for the IMIA Yearbook 2007.Current research in the field of bioinformatics is characterized by careful evaluation of methods and by improved integration of methods into clinical workflows. Ongoing research on genetic causes of diseases is performed on more and better sources of reference data (genome sets and respective annotations), but is still hampered by insufficient, lacking or biased patient data. The application area of bioinformatics has been broadened, leading to amendment or even replacement of traditional methods in fields like characterization of microorganisms. Researchers carry out thorough statistical analyses in order to ensure quality and methodological correctness of new methods based on bioinformatic approaches which are more and more competitive compared to well-established techniques.The best paper selection of articles on bioinformatics shows examples of excellent research on methods concerning original development as well as quality assurance of previously reported studies. The crucial role of reliable and comprehensive data sources is affirmed, while technical development draws attention to the increasing problem of comparability of data derived some years ago with weaker equipment and those that are of up-to-date quality.
Keywords: Medical informatics; International Medical Informatics Association; yearbook; bioinformatics